Awareness of testicular cancer among young men: A literature review. Issue 1 (17th July 2020) - Bresciani, Martina; Boarin, Mattia; Facconi, Ilaria; Manara, Duilio F.; Villa, Giulia
Abstract: What is the degree of knowledge and awareness regarding testicular cancer and what interventions may improve information about testicular cancer in the male population? Testicular cancer incidence rates are increasing among young men, who typically demonstrate poor awareness and a lack of knowledge about this disease. Although testicular self‐examination might be an effective method for early detection, few people know about this process or regularly perform it. This lack of examination could delay the diagnosis, which would affect treatment outcomes and mortality rates. A literature review was conducted starting from a bibliographic research in the major databases, and 450 documents were identified. The final analysis included 19 studies and found that men feel anxious about testicular cancer, which leads to a delay in their diagnosis and treatment, especially in developing countries. A widespread lack of awareness and knowledge about testicular cancer and self‐examination exists in these nations. Few males performed testicular self‐examination; most considered this procedure to be an invasion of their privacy and masculinity. The most effective tools to disseminate awareness about testicular cancer prevention were television, radio and YouTube. It is important to educate young males to spread information and improve awareness and knowledge about testicular cancer and self‐examination. However, the support of regular self‐examination is controversial, as this practice might also produce more harm than benefits due to the resulting false positives, fear and anxiety. Regular testicular cancer screening is therefore recommended in limited populations, including patients with risk factors, such as cryptorchidism or a family history of this cancer.